2013
DOI: 10.1097/rti.0b013e3182828f89
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Enhancement Magnetic Resonance Imaging in Nonischemic Myocardial Disease

Abstract: This review highlights the role of delayed enhancement magnetic resonance imaging for the diagnosis of patients with nonischemic myocardial disease. The authors discuss the use of delayed enhancement for differentiation between ischemic and nonischemic myocardial disease and for narrowing the differential diagnosis when nonischemic etiologies are suspected. In addition, special focus is given to the prognostic applications of delayed enhancement magnetic resonance imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Global involvement of myocardial inflammation in CS may also occur. However, atrial thickening and atrial LGE are more commonly observed in amyloidosis and may help differentiate this condition from CS (83). Definitive involvement by amyloidosis is established histologically on the basis of the presence of apple-green birefringence at polarizing light microscopy (Fig 20).…”
Section: Amyloidosismentioning
confidence: 99%
“…Global involvement of myocardial inflammation in CS may also occur. However, atrial thickening and atrial LGE are more commonly observed in amyloidosis and may help differentiate this condition from CS (83). Definitive involvement by amyloidosis is established histologically on the basis of the presence of apple-green birefringence at polarizing light microscopy (Fig 20).…”
Section: Amyloidosismentioning
confidence: 99%
“…Approximately 7-8 minutes after contrast material injection, a variable-inversiontime scout sequence is performed to select the inversion time that nulls the normal myocardial signal (a typical inversion time is 200-300 msec). Imaging acquisition 10-15 minutes after injection is performed with a short-axis myocardial signal-nulled T1-weighted sequence from the base toward the apex (44). Of note, superior contrast between normal and abnormal myocardium on contrast material-enhanced images has been shown 5-8 minutes after gadolinium administration instead of the imaging delay of 10-15 minutes generally used in contrast-enhanced cardiac MR imaging.…”
Section: Technical Considerations In Cardiac Mr Imagingmentioning
confidence: 99%
“…Although catheter ablation reduces recurrences of sustained MMVT in patients with ischaemic cardiomyopathy, a reduction in mortality has yet to be demonstrated [150]. Catheter ablation has also been successfully used in patients with non-ischaemic cardiomyopathy where the ablation target is often on the epicardial surface of the ventricles and the procedure may be more complex [151][152][153][154][155][156]. The long-term effectiveness of catheter ablation for non-ischaemic cardiomyopathies has been less well studied than for ischaemic cardiomyopathies.…”
Section: Catheter Ablationmentioning
confidence: 99%